2009
DOI: 10.1016/j.aprim.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Permanencia del efecto de una intervención de mejora de calidad en el seguimiento prolongado de pacientes hipertensos (CICLO-RISK STUDY)

Abstract: Quality improvement intervention was associated with reductions in cardiovascular risk factors and cardiovascular risk in post intervention evaluations with a tendency to decrease the effect achieved in the end evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, in a study similar to ours with the aim to reduce cardiovascular risk in hypertensive patients, Gomez Marcos and colleagues 30 showed that the differences between the intervention and control groups in SBP and DBP values were larger, −9.0 mm Hg (95% CI −11.3 to −6.7) and −3.9 mm Hg (95% CI −5.4 to −2.4), respectively. The greater reduction of BP values in this study compared with our analysis of an entire hypertensive population could be explained by their recruitment of only 849 hypertensive patients with a long-term regular follow-up in the PHCTs.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…On the other hand, in a study similar to ours with the aim to reduce cardiovascular risk in hypertensive patients, Gomez Marcos and colleagues 30 showed that the differences between the intervention and control groups in SBP and DBP values were larger, −9.0 mm Hg (95% CI −11.3 to −6.7) and −3.9 mm Hg (95% CI −5.4 to −2.4), respectively. The greater reduction of BP values in this study compared with our analysis of an entire hypertensive population could be explained by their recruitment of only 849 hypertensive patients with a long-term regular follow-up in the PHCTs.…”
Section: Discussionmentioning
confidence: 49%
“…We have not been able to determine if the improvements are sustainable after the intervention was finalised, though a study carried out in Spain suggested that the effects of quality interventions on hypertension tend to decrease over time. 30 Also, we do not know if a better hypertension control in the intervention group is related to a decrease in cardiovascular morbimortality.…”
Section: Discussionmentioning
confidence: 96%
“…Sin duda, siguen siendo necesarios más estudios que aporten evidencia sobre la mejora de los resultados en salud de las personas en tratamiento tras el uso de GPC [3][4][5] . En nuestro entorno existen estudios sobre la actitud del personal médico sanitario que indican una variabilidad en las decisiones clínicas con un bajo nivel de adherencia a las recomendaciones de las GPC 6,7 . El proyecto EDUCAGUIA estudió la efectividad de una estrategia educativa basada en juegos e-EDUCAGUIA 8 para mejorar la adherencia a las recomendaciones de las guías en la prescripción de antibióticos por parte de residentes de Medicina Familiar y Comunitaria (MFyC) en nuestro entorno, encontrando efectos positivos a corto plazo sobre los conocimientos y habilidades en la toma de decisiones sobre terapia antimicrobiana, aunque la adherencia a los juegos educativos fue moderada y las pérdidas en el seguimiento fueron elevadas y con diferencias de género.…”
Section: Originalunclassified